Promoción y prevención en salud oral en estudiantes con condiciones especiales de salud de la Fundación Tinkuyay (2023)
Health promotion and disease prevention are all procedures aimed at any population to improve or maintain their living or health conditions. It is important to strengthen oral health activities at the most influential stages of children’s lives, enabling them to develop attitudes and skills that are sustainable for life, because poor oral health can have a detrimental effect on children’s quality of life, school performance and future life.